Short-term metabolism of biologically incorporated 125I ingested by olive flounder (Paralichthys olivaceus). (April 2020) - Imai, Shoko; Tani, Takashi; Ishikawa, Yoshio; Tako, Yasuhiro; Takaku, Yuichi; Hisamatsu, Shun'ichi
Abstract: Iodine-129 with a long half-time of 1.6 × 10 7  y was discharged into the Pacific Ocean during the final safety tests of the first commercial nuclear fuel reprocessing plant in Japan, at Rokkasho, Aomori Prefecture. Olive flounder ( Paralichthys olivaceus ) is an important fishery along this coast. It is necessary to determine whether 129 I accumulates in this species to assess the possible public acceptance. We developed a short-term metabolism model of 125 I in the flounder using retention data for 1–6 days after the olive flounder had ingested a freshwater fish species, medaka ( Oryzias latipes ), that had been labeled with 125 I by keeping them in water containing 125 I for 7 days. A single compartment model constructed from whole-body retention data for 125 I in the olive flounder, excluding the gastrointestinal tract and its contents, revealed a biological half-time of 2.9 days for 125 I. When the gill and other tissues were separated to individual compartments, the biological half-time in the gill was three times longer than that in the other tissue, though the half-time in the gill is not statistically significant. The distribution of 125 I among various tissues in the flounder 6 days after the ingestion of labeled medaka once a day for 6 days differed from that of stable I, suggesting that the biological half-time is longer in certain tissues. Further study is necessary to elucidate the metabolism of radioiodine in the flounder. Highlights: Olive flounder ( Paralichthys olivaceus ) is an important coastal fishery in Japan. We measured metabolism of 125 I in this species in a laboratory experiment. Olive flounders were examined 1–6 days after ingesting medaka that were fed 125 I. The biological half-time of 125 I was 2.9 days in the flounder. Biological half-time was up to three times longer in some tissues, like the gills.